Economic Empowerment of Housewives Based on OPOR (One Product in One RT) in Pojok Village of Magetan Regency, Using the Asset-Based Community-Driven Development (ABCD) Approach - Yuniar Farida; Wika Dianita Utami; Aris Fanani; Latifatun Nadya Desinaini; Silvia Kartika Sari (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Nowadays, the improvement in resources, especially among women, is considered. One of the efforts to empower women in the village can be done through the assistance of Micro, Small, and Medium Enterprises (MSMEs). This research-based community service aims to assist the community, especially women (housewives) in Pojok Village of Magetan Regency, in developing home businesses. This community service is carried out by using ABCD approach, which is an approach to understanding and internalizing assets, potential, strength, and utilization independently and optimally. The results of the community service carried out by researchers have positive impact to the community and it fosters a high desire and enthusiasm to make changes for the better in the development of marketing businesses, both during the mentoring process and post-mentoring so that the economy in Pojok Village, Magetan Regency can increase